Analisis Pencemaran Biologis Perairan Pantai Wisata Holtekamp Berdasarkan Kepadatan Bakteri Coliform - Ayer, Popi Ida Laila; Mandey, Vera K.; Rejauw, Korinus; Wanimbo, Efray; Warpur, Maklon (Cenderawasih University, 2023)
Holtekamp Sea is located in Youtefa Bay, directly connected to the Acai River, which carries waste from land-based activities such as bathing, washing, toilet, livestock farming, ponds, and agriculture. This will affect the bacteriological quality of the Holtekamp Coastal Waters. This study was conducted to analyze the quality of coliform bacteria density a an indicator of biological pollution in the waters of Holtekamp Beach Seawater sample were collected in April 2023. Bacteriological analysis was performed at Papua Regional Health Laboratory using the Most probable number (MPN) method. The research result show that the Nitrate range at stations I to III is 1.70, exceeding the water quality standard of 0.008 according to Decree of Minister of Environment No. 51 of 2004. Furthermore, coliform at stations I to III, it is more than equal to 1898 MPN/100 mL. Meanwhile, the total density of fecal coliform bacteria at stations I and II is 20 MPN/100 mL, and station III is 9 MPN/100 mL. According to Decree of the Minister of Environment No. 51 of 2004, the presence of coliform bacteria in the waters of Holtekamp Beach has exceeded the water quality standard. Thus, the total concentration of nitrate and coliform bacteria density indicates poor water quality or contamination